1978
DOI: 10.1111/j.1399-6576.1978.tb01293.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Naloxone Reversal on CO2 Output, Oxygen Uptake and Cardiac Index During Recovery from Fentanyl‐Supplemented Anaesthesia

Abstract: For reversal of contingent residual narcotic depression after fentanyl administration during balanced anaesthesia, the effect of 0.08 mg of naloxone on GOz output, O2 uptake and cardiac index was studied immediately after extubation. This dose maintained normocapnia (5.7 kPa) during early recovery, while in the control group slight hypercapnia was present (6.0 kPa). No significant differences, however, could be detected between the groups in GO2 output, O2 uptake or cardiac index. When 0.16 mg of naloxone was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…2 Increases in heart rate and blood pressure were also noted and are consistent with previous reports. 12, 13 In one study, a significant and prompt increase in heart rate, cardiac index, and cardiac work in response to naloxone was noted. 12 Another trial observed an increase in cardiac index following administration of naloxone and attributed this to the increased work generated by the heart after improved ventilation that followed naloxone reversal of opioid effects.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…2 Increases in heart rate and blood pressure were also noted and are consistent with previous reports. 12, 13 In one study, a significant and prompt increase in heart rate, cardiac index, and cardiac work in response to naloxone was noted. 12 Another trial observed an increase in cardiac index following administration of naloxone and attributed this to the increased work generated by the heart after improved ventilation that followed naloxone reversal of opioid effects.…”
Section: Discussionmentioning
confidence: 97%
“…12 Another trial observed an increase in cardiac index following administration of naloxone and attributed this to the increased work generated by the heart after improved ventilation that followed naloxone reversal of opioid effects. 13 The increase in heart rate and blood pressure following administration of naloxone has been attributed to catecholamine release. 12, 13 Excess catecholamine release following naloxone administration has been implicated in the development of serious adverse effects such as arrhythmias, pulmonary edema, and cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[64][65][66] In the post-operative period, Tigerstedt and Tammisto observed that when patients were given 0.08 mg naloxone after anesthesia with fentanyl, there were no significant differences between the naloxone and control groups in CO 2 output, O 2 uptake or cardiac index. 67 However when 0.16 mg of naloxone was similarly administered to patients 10 min after fentanyl-supplemented balanced anesthesia, there were significant increases in respiratory rate, minute volume, CO 2 output and O 2 uptake, as well as an increase in the cardiac index, thought to reflect a metabolic increase that may not be tolerated in all patients, thus careful titration was recommended.…”
Section: Severe Cardiovascular Eventsmentioning
confidence: 99%
“…Significant increases in cardiac work have been shown following narcotic reversal with naloxone. [13][14][15] These authors concluded that a reduced dosage regimen should be adopted for naloxone use. However, Prough et al lo reported the occurrence of pulmonary oedema in two patients given 0.1 mg doses of naloxone.…”
Section: Discussionmentioning
confidence: 99%